Heat shock proteins and their role in the immune regulation of inflammation - Van Eden, Willem (Henry Stewart Talks, 2012)
Evolutionary conservation of heat shock proteins, Models of autoimmunity and other inflammatory conditions, Heat shock proteins induce regulatory T cells, Heat shock proteins are targets of immunotherapeutic vaccines